Isolation and Characterization of a Novel H1.2 Complex That Acts as a Repressor of p53-mediated Transcription - Kim, Kyunghwan (American Society for Biochemistry and Molecular Biology, 2008)
Linker histone H1 has been generally viewed as a global repressor of transcription by preventing the access of transcription factors to sites in chromatin. However, recent studies suggest that H1 can interact with other regulatory factors for its action as a negative modulator of specific genes. To investigate these aspects, we established a human cell line expressing H1.2, one of the H1 subtypes, for the purification of H1-interacting proteins. Our results showed that H1.2 can stably associate with sets of cofactors and ribosomal proteins that can significantly repress p53-dependent, p300-mediated chromatin transcription. This repressive action of H1.2 complex involves direct interaction of H1.2 with p53, which in turn blocks p300-mediated acetylation of chromatin. YB1 and PURα, two factors present in the H1.2 complex, together with H1.2 can closely recapitulate the repressive action of the entire H1.2 complex in transcription. Chromatin immunoprecipitation and RNA interference analyses further confirmed that the recruitment of YB1, PURα, and H1.2 to the p53 target gene Bax is required for repression of p53-induced transcription. Therefore, these results reveal a previously unrecognized function of H1 as a transcriptional repressor as well as the underlying mechanism involving specific sets of factors in this repression process.